A Palm Sap-Based Brown Sugar Business Development Strategy Based on the Business Model Canvas - Amanda Putri Salsabila; Wahyu Syarvina; Aqwa Naser Daulay (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2025)
Through the nine elements of the business model canvas, this study seeks to identify or develop a strategy for the development of a palm sap-based brown sugar business at CV. Ritawati Silau Rakyat Brown Palm Sugar, Serdang Bedagai, Indonesia The goal is to establish partnerships to work together to increase revenue and market share. A qualitative approach combined with phenomenological analysis was used to investigate the phenomenon that arises in the field connected to the growth of a brown sugar enterprise based on palm sap in Silau Rakyat Village. Results of the Business Model Canvas Analysis at CV. Ritawati Palm Brown Sugar is a customer segment, local consumers who are looking for natural sweeteners. It has a distinctive taste and authentic aroma. Its distribution is carried out through collectors for the local market. Building customer relationships and communication directly and through social media. Revenue streams: The main source of income is the sale of palm sap brown sugar. Key Resources: The main resource includes palm sap water as a raw material. Key activities, including procurement of raw materials. Key Partnership: Partnership with oil palm farmers. Cost structure, including production, distribution, taxes, and packaging. However, challenges, such as seasonal dependence and raw material availability, remain. The solution to these challenges is to implement key partnerships in the form of procuring palm sap from surrounding areas to address declining palm sap production in Silau Rakyat Village.